Factors Influencing Students' Choice Of Private Higher Education Institutions In Malaysia - Leong, Lilian Li Ling (2008)
This paper researched on the issues of consumer buyer behaviour towards choice of private higher education institution. It attempted to understand the sources of information sought and associated influences that affect students when considering a particular institution and also factors which ultimately determined the final decision to enroll.